Estimation of phytochemicals, antioxidant, antimicrobial, and brine shrimp lethality activities of Valeriana jatamansi Jones - Indra Ojha; Khaga Sharma (Bibechana)
Herbal medicine has been widely utilized in traditional medicine for treating various ailments. This study aimed to quantify the phenolic, flavonoid, and tannin content in different plant extracts, assess their antioxidant capacity, and evaluate their antimicrobial efficacy. Among the extracts tested, methanol exhibited the highest total phenolic content (TPC) at 166.5 ± 2.0 mg GAE/g and total flavonoid content (TFC) at 103.87 ± 5.47 mg QE/g, whereas hexane displayed the lowest TPC (16.03 ± 2.22 mg GAE/g) and TFC (8.27 ± 3.88 mg QE/g). The methanolic extract demonstrated the strongest antioxidant activity with an IC50 of 103.3 ± 1.53 μg/mL, compared to the hexane extract's IC50 of 524.7 ± 0.89 μg/mL. Antimicrobial testing revealed that aqueous, ethanolic, and hexane extracts effectively inhibited Klebsiella pneumoniae with a zone of inhibition of 17 mm, comparable to the positive control neomycin (24 mm). The ethanolic extract showed substantial minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against K. pneumoniae and Staphylococcus aureus (3.12 mg/mL and 6.25 mg/mL, respectively), relative to the control (0.0078 mg/mL and 0.015 mg/mL). Additionally, cytotoxicity assays showed LC50 values of 1077.78 μg/mL for the ethanolic and 1905.46 μg/mL for the methanolic extract. These findings suggest that the studied plant extracts, particularly methanolic and ethanolic, have significant bioactive potential, positioning them as promising sources for future drug development against infectious diseases.